Desenvolvimento e implementação de malhas adaptativas bloco-estruturadas para computação paralela em mecânica dos fluidos - Lima, Rafael Sene de (2012)
The numerical simulation of fluid flow involving complex geometries is greatly limited by the required spatial grid resolution. These flows often contain small regions with complex motions, while the remaining flow is relatively smooth. Adaptive mesh refinement (AMR) enables the spatial grid to be refined in local regions that require finer grids to resolve the flow. This work describes an approach to parallelization of a structured adaptive mesh refinement (SAMR) algorithm. This type of methodology is based on locally refined grids superimposed on coarser grids to achieve the desired resolution in numerical simulations. Parallel implementations of SAMR methods offer the potential for accurate simulations of high complexity fluid flows. However, they present interesting challenges in dynamic resource allocation, data-distribution and load-balancing. The overall efficiency of parallel SAMR applications is limited by the ability to partition the underlying grid hierarchies at run-time to expose all inherent parallelism, minimize communication and synchronization overheads, and balance load. The methodology is based on a message passing interface model (MPI) using the recursive coordinate bisection (RCB) for domain partition. For this work, a semi-implicit projection method has been implemented to solve the incompressible Navier Stokes equations. All numerical implementations are an extension of a sequential Fortran 90 code, called "AMR3D", developed in the work of Nós (2007) .The efficiency and robustness of the applied methodology are verified via convergence analysis using the method of manufactured solutions. Validations were performed by simulating an incompressible jet flow and a lid driven cavity flow.